Willingness to pay for reducing crowding effect damages in marine parks in Malaysia - Ahmad, Siti Aznor; Hanley, Nick (World Scientific Publishing Co., 2009)
Marine Parks are established to protect an area of the sea zoned as a sanctuary for the protection of its marine eco-systems, especially coral reef and its associated fauna and flora, like sea grass bed, mangrove and the sea shore.In Malaysia, there are 6 marine parks to-date.The establishment of marine parks also attracts more tourists to the areas.For example, the number of visitors to Payar Marine Park increased tremendously from 3,668 visitors in 1990 to 133,775 visitors in 2002.However, too many tourists are thought by scientists to have damaged the coral reefs.This paper will estimate how much visitors are willing to pay to reduce damages to three marine parks in Malaysia; Payar, Redang and Tioman Marine Park.Willingness to pay estimates were obtained from the visitors using a double-bounded dichotomous choice version of the Contingent Valuation method.